2020
DOI: 10.1186/s43088-019-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using marine macroalgae Padina sp. and its antibacterial activity towards pathogenic bacteria

Abstract: Background: Marine algae used as a food source for ocean life and range in color from red to green to brown grow along rocky shorelines around the world. The synthesis of silver nanoparticles by marine alga Padina sp. and its characterization were fulfilled by using UV-visible spectrophotometer, Fourier transform infrared spectroscopy, scanning electron microscopy and field emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. Results: UV-visible absorption spectrum revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(83 citation statements)
references
References 29 publications
(35 reference statements)
8
73
0
2
Order By: Relevance
“…is indicative of Cl À ion oxidation of Ag 0 to Ag + ions. 55,59 Citrate capping agents offer no protection to Cl À oxidation of the AgNPs. The triangular and spherical Ag-Cit-SOA-PC without thiols underwent slower surface oxidation and Ag + ion dissolution.…”
Section: Effect Of Chloride Ions Ph and Thiolates On Nanoparticle Smentioning
confidence: 99%
See 1 more Smart Citation
“…is indicative of Cl À ion oxidation of Ag 0 to Ag + ions. 55,59 Citrate capping agents offer no protection to Cl À oxidation of the AgNPs. The triangular and spherical Ag-Cit-SOA-PC without thiols underwent slower surface oxidation and Ag + ion dissolution.…”
Section: Effect Of Chloride Ions Ph and Thiolates On Nanoparticle Smentioning
confidence: 99%
“…47,48 Although these synthetic methods have produced AgNPs shaped as spheres, 49 cubes, 50 bipyramids, 51 stars, 52 nanoprisms, 53 triangular plates 53 these methods are energy-intensive, the size and shape distributions are not always homogenous, and chemicals used can be toxic. Consequently, this has given rise to alternative green synthetic approaches employing biological entities such as microorganisms 10,12,54,55 and plant extracts 4, [56][57][58][59][60][61][62][63] to replace more complex syntheses of AgNPs free from toxic capping agents and hazardous byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Most of all indicated that the methanol extraction yielded more compared to hexane and ethyl acetate. [7,25,26]. Ethyl acetate and methanol were determined as the most effective organic solvent for the isolation of antibacterial compounds [27,28].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Cyanobacteria is an incredible old group of prokaryotic organisms that produces a variety of secondary metabolites such as antibiotic, cytotoxic, immunosuppressive and enzyme inhibiting agents [4][5][6]. Bioactive compounds are defined as the secondary metabolites that can be isolated and purified from the microalgae, plant, microbes and other organisms that has ability in biological activities [7]. The production of bioactive compounds from microalgae can be beneficial in pharmaceutical industry [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Marine bioactives can be obtained from various sources such as marine plants/seaweeds, microorganisms, sponges, etc. Among the various sources, seaweeds are reported to possess bioactive compounds having high antioxidant, antimicrobial, antiviral, antidiabetic, anti‐inflammatory, antiviral, antitumor properties, etc., which is why they have gained the status of “superfood” recently (Bhuyar, Rahim, Sundararaju, Maniam, & Govindan, 2020; Bhuyar, Rahim, Sundararaju, Ramaraj, et al, 2020; Gormley & Holm, 2010; Gupta & Abu‐Ghannam, 2011). Among all (green, red, and brown), brown seaweeds, which is the second most abundant group, is reported to possess comparatively high structural diversity with polyphenols, polysaccharides, bioactive peptides, polyunsaturated fatty acids, etc.…”
Section: Introductionmentioning
confidence: 99%